Blinatumomab as first salvage versus second or later salvage in adults with relapsed/refractory B‐cell precursor acute lymphoblastic leukemia: Results of a pooled analysis. (18th March 2021) - Topp, Max S.; Stein, Anthony S.; Gökbuget, Nicola; Horst, Heinz‐August; Boissel, Nicolas; Martinelli, Giovanni; Kantarjian, Hagop; Brüggemann, Monika; Chen, Yuqi; Zugmaier, Gerhard
Abstract: Background: Blinatumomab is a BiTE ® immuno‐oncology therapy indicated for the treatment of patients with relapsed or refractory (r/r) B‐cell precursor (BCP) acute lymphoblastic leukemia (ALL). Aims: To assess the efficacy and safety of blinatumomab as first salvage versus second or later salvage in patients with r/r BCP ALL. Materials & Methods: Patient‐level pooled data were used for this analysis. In total, 532 adults with r/r BCP ALL treated with blinatumomab were included (first salvage, n = 165; second or later salvage, n = 367). Results: Compared with patients who received blinatumomab as second or later salvage, those who received blinatumomab as first salvage had a longer median overall survival (OS; 10.4 vs. 5.7 months; HR, 1.58; 95% CI, 1.26–1.97; P < .001) and relapse‐free survival (10.1 vs. 7.3 months; HR, 1.38; 95% CI, 0.98–1.93; P = .061), and higher rates of remission (n = 89 [54%] vs. n = 150 [41%]; odds ratio, 0.59; 95% CI, 0.41–0.85; P = .005), minimal residual disease response (n = 68 [41%] vs. n = 118 [32%]), and allogeneic hematopoietic stem cell transplant (alloHSCT) realization (n = 60 [36%] vs. n = 88 [24%]), and alloHSCT in continuous remission (n = 33 [20%] vs. n = 52 (14%]). In a subgroup analysis, there was no apparent effect of prior alloHSCT on median OS in either salvage group. The safety profile of blinatumomab was generally similar between the groups; however, cytokine release syndrome, febrile neutropenia, and infection were more frequent with second or later salvage than with first salvage. Discussion: In this pooled analysis, the logistic regression analyses indicated greater benefit with blinatumomab as first salvage than as second or later salvage, as evident by the longer median OS, longer median RFS, and higher rates of remission. Conclusion: Overall, blinatumomab was beneficial as first salvage and as second or later salvage, but the effects were favorable as first salvage. Abstract : This pooled analysis of three clinical studies assessed the efficacy and safety of blinatumomab as first salvage versus second or later salvage in patients with relapsed or refractory (r/r) B‐cell precursor (BCP) acute lymphoblastic leukemia (ALL). Compared with patients who received blinatumomab as second or later salvage, those who received blinatumomab as first salvage had a longer median overall survival, relapse‐free survival, and higher rates of remission, minimal residual disease response, and allogeneic hematopoietic stem cell transplant (alloHSCT) realization. Overall, blinatumomab was beneficial as first salvage and as second or later salvage, but the effects were favorable as first salvage.